2003
DOI: 10.1029/2003gl017585
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a D″ discontinuity in the south Atlantic using PKKP

Abstract: [1] A strong arrival in the early coda of major-arc PKKP ab is observed on recordings of earthquakes in the Banda Sea region from the short-period, small-aperture Yellowknife array. The arrival has a move-out close to PKKP ab with an average delay of $12 s. We show that the phase is most likely an underside reflection from a D 00 discontinuity above the PKKP reflection point at the core-mantle boundary beneath the southern Atlantic on the edge of the African superplume. Differential travel times between PKKP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The ab and bc branches of PKKP have been commonly observed in previous studies (Rost & Revenaugh, 2003), while the recent findings by Chen et al (2022) and Russell et al (2022) have reported the presence of diffracted PKKPab waves with long diffraction path lengths (Figures 1a-1c). However, for PmKP phases (m ≥ 3), only the ab and diffracted ab branches could be observed (Figures 1b-1d).…”
Section: Global Seismic Data Setsupporting
confidence: 62%
See 1 more Smart Citation
“…The ab and bc branches of PKKP have been commonly observed in previous studies (Rost & Revenaugh, 2003), while the recent findings by Chen et al (2022) and Russell et al (2022) have reported the presence of diffracted PKKPab waves with long diffraction path lengths (Figures 1a-1c). However, for PmKP phases (m ≥ 3), only the ab and diffracted ab branches could be observed (Figures 1b-1d).…”
Section: Global Seismic Data Setsupporting
confidence: 62%
“…The ab and bc branches of PKKP have been commonly observed in previous studies (Rost & Revenaugh, 2003), while the recent findings by Chen et al. (2022) and Russell et al.…”
Section: Global Seismic Data Setsupporting
confidence: 54%
“…PKKP has been used to study CMB structure in past studies [ Doornbos , 1980; Earle and Shearer , 1997; Rost and Revenaugh , 2003b]. PKKP energy is dominant in short‐period seismograms and is often the dominant phase arriving about 1000s after direct P (see Figure 2).…”
Section: Pkkpabdiffmentioning
confidence: 99%
“…This perhaps implies that PKKP is indeed difficult to isolate and given its multiple branches, an assignment to its traveltime shift due to CMB topography, neglecting effects from lowermost mantle and outer core velocity variations, is a rather simplified assumption as many effects can lead to almost synchronous arrivals [e.g. Earle andShearer, 1997, Rost andRevenaugh, 2003]. We note that difficulties isolating separate branches of the PKKP phase would be reduced when using higher-frequency waveforms, as usually done when using ray theory, [e.g.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%